Highly porous thin films obtained by spray-gel technique - Solís, José (2004)
Combining the spray pyrolysis and the sol-gel techniques (spray-gel) gives the possibility to produce very rough and highly diffuse films, under appropriate conditions. This technique is suitable for producing multifunctional metal oxides for gas-sensing, electrochromism, microbattery, and photocatalysis applications; due to the fact that it yields a large interface between a solid and a gaseous/liquid medium. The process basically consists in producing an aerosol from a gel, which is sprayed over a hot substrate, where the film is going to grow. In this work we present the results on highly porous SnO2, WO3, and phosphotungstic acid (PWA) thin films obtained by spray-gel.